PRELIMINARY STUDES ON THE SALT TOLERANCE OF MOONG ( Phaseolus aureus, Roxb. var ,RS-5), SEEDS AT GERMINATION STAGE - Singh, Megh; Lal, p; Singh, K S (Annals of Arid Zone, 2016)
A study was carried out to see the effect of salt concentration and SAR levels on the germination of Moong (Phaseolus aures Roxb. Var. R5-5) seeds and to know if their salt tolerance can be increased by dipping them in solutions of salts, hormone and micronutrients. The salt concentration upto 22.5 m. eq/l did not affect the germination at . all, 50.0 m. eq/l affected slightly while 100.0, m. eq/l resulted in drastic, reduction. Similar was the trend with SAR. Pre-soaking treatments at the mentioned concentration and soaking time did not help in overcoming the effect of higher level of EC and SAR.